Gravity and Magnetic Constraints on the Crustal Structure of the Ceará Plateau, Brazilian Equatorial Margin - Moura, Denise Silva de; Molina, Eder Cassola; Marangoni, Yara Regina; Jovane, Luigi (Frontiers in Earth Science, 2019)
The Brazilian Equatorial Margin is a transform passive margin with long fracture zones and several seamounts, including the largest one, the Ceará Plateau. This is a complex and poorly recognized area, with few available geophysical data. Gravity and magnetic data from the Equant I Project, seismic published lines and other previous studies are used to make several models and analyses. We recognized gravity and magnetic anomalies related to a denser, magnetized basement, internally comprised of two magmatic highs. Through gravity and magnetic forward modeling, we estimated the basement surface between 800 and 6000 m and the Mohorovičić discontinuity about 22-23 km below the Ceará Plateau. We also present and discuss the position of the continent-ocean boundary 40 km away from the continental shelf, placing the plateau at the oceanic crust domain, and the area of the transitional crust, with an extension of 40-50 km, formed during the rifting phase of the Atlantic Ocean opening.